A Real-World Comparison Between Adjuvant Docetaxel with Cyclophosphamide (TC) and Anthracycline–Taxane Chemotherapy in Early HER-2 Negative Breast Cancer. - Giffoni de Mello Morais Mata, Danilo; Pezo, Rossanna C.; Chan, Kelvin K. W.; Menjak, Ines; Eisen, Andrea; Trudeau, Maureen (Current Oncology, 2025)
Background: Anthracycline–taxane chemotherapy is the gold standard in high-risk breast cancer (BC), despite the potential risk of congestive heart failure (CHF). A suitable alternative for anthracycline-sparing chemotherapy is through the combination of docetaxel and cyclophosphamide (TC). Methods: Through a retrospective study of stage I-III HER2-negative BC, using administrative databases, we analyzed a total of 10,634 women treated with adjuvant chemotherapy in Ontario, Canada, between 2009 and 2017. We compared TC versus standardized anthracycline–taxane chemotherapies (ACT and FEC-D). We investigated the overall survival (OS), and explored the incidence of CHF, emergency department (ED) visits and febrile neutropenia. Results: With a median follow-up of 5.5 years, the 5-year analysis showed an increased OS in patients treated with TC, versus those treated with ACT, HR 0.77 (0.63–0.95, p = 0.015). Among ER+ BC, there was an increased OS in patients treated with ACT and FEC-D, versus those treated with TC, HR 0.70 (0.52–0.95, p = 0.021) and HR 0.71 (0.56–0.91, p = 0.007), respectively. There were no substantial differences in CHF, between TC and anthracycline-based treatments. Patients treated with TC and FEC-D had more ED visits, compared to those treated with ACT. Conclusion: Our study shows that anthracycline–taxane regimens were the most commonly prescribed adjuvant chemotherapy options in HER2-negative BC. Women who received ACT had the lowest OS, likely due to their unfavorable pathology.